UJI AKTIVITAS ANTIBAKTERI Staphylococcus aureus BERDASARKAN PERBEDAAN JENIS PELARUT EKSTRAK BIJI BUAH PEPAYA (Carica papaya L.) - Lisa Anjani, Ni Putu; Suyasa, I Nyoman Gede; Habibah, Nur; Purna, I Nyoman (Poltekkes Kemenkes Denpasar, 2025)
Staphylococcus aureus is an opportunistic pathogenic bacteria on the surface of the skin that causes impetigo. Treatment therapy for impetigo can be done by administering natural medication from papaya seeds (Carica papaya L). This study aims to determine the antibacterial activity of Staphylococcus aureus papaya seed extract based on the different types of extract solvents used. This research is true experimental research with a posttest only control design research form. The research method used was the disk diffusion method with three treatments of papaya seed extract, namely 96% ethanol extract, ethyl acetate and n-hexane, positive control using chloramphenicol and negative control using 96% ethanol, ethyl acetate and n-hexane. The research results showed that each papaya seed extract treatment was able to inhibit Staphylococcus aureus with an inhibition zone of 96% ethanol extract of 18.09 mm, ethyl acetate extract of 7.93 mm, n-hexane extract of 0.36 mm. The One Way Anova test showed a value of ρα(0.05) so that there was a significant difference in the diameter of the inhibition zone in each extract treatment. The Tukey test showed that there were significant differences in the inhibition zone of Staphylococcus aureus bacteria (ρα(0.05)) in almost all treatments. The conclusion of this research is that there is a difference in the antibacterial activity of 96% ethanol extract, ethyl acetate extract and n-hexane extract of papaya seeds on the growth of Sthaphylococcus aureus bacteria.